Formulation and Characterization of Piroxicam Emulgel for Topical Drug Delivery: Pharmaceutical Science-Pharmacy for better health - Dr. Shaikh Siraj N; Shahid Raza Mohd Aslam Ansari; Dr.G.J.Khan; M. Siddik N. Patel; Irshad Ahmad Mohd. Salim; Dr. Rahul Laxman Jadhav (International Journal of Life Science and Pharma Research, 2022)
The aim and objective of this research work was to formulate and evaluate Piroxicam Emugel for topical drug delivery. Various concentration of gelling agent were used for preparation of Piroxicam Emugel along with emulsifiers Tween-80 and Span-80 with glycerine as a humectants. The Clove oil and eucalyptus oil were used as permeation enhancer. The formulated Emulgel was characterized for their physical appearance, pH determination, spreadability, extrudability, drug content, in vitro drug release and stability studies. According to our results, the range of pH of the formulations was from 5.6±0.2 to 6.8±0.3 for final batches which is considered acceptable. Formulation F3, F4, F6 and F7 spreadability was found to be 32.03 ± 0.54 g.cm/sec, 30.79±0.2 g.cm/sec, 26.41±0.51 g.cm/sec and 30.44±0.6 g.cm/sec respectively. The Formulation F5 and F8 was prepared with higher concentration of carbopol i.e. 1.5 g were of in stiff category and the spreadabilty value found to be 18.14±0.36 g.cm/sec and 20.30±0.34 g.cm/sec respectively. The percentage swelling index was (F5, F6, F7 and F8) found to be 44.24 %, 27.35%, 31.98 % and 46.38 respectively. Extrudability of Formulation F5 and F8 was less i.e. 17.32± 0.5 gm/cm2 and 20.39±0.58 gm/cm2 respectively as containing higher concentration of polymer. Formulation F3, F4, F6, F7 having optimum concentration of polymer extrudability was good i.e. 30.47±0.52 gm/cm2, 27.39±0.6 gm/cm2, 29.49±0.56 gm/cm2 and 26.90±0.6 gm/cm2 respectively. Extrudability was decreased with an increase in concentration of Carbopol. Invitro drug release (98.45% in 8h) from the Emulgel, batch F7 was concluded as optimized batch. Drug release was in following order F5< F1< F3< F2< F4< F8 < F6 < F7. Presence of two Penetration enhancer’s Clove oil and Eucalyptus oil has resulted in better performance as compared to other formulations. All these developed emugel formulation have acceptable physical properties, hence F7 can be considered as the optimized formulation. From this research, the formulated Emulgel of Piroxicam would be an effective alternative to conventional delivery of Piroxicam for the management of pain and inflammation.